CDCP1 promotes the malignant phenotypes of nasopharyngeal carcinoma via the Wnt/β-catenin signaling pathway - Guoliang Bie; Shuang Cheng; Weiping Huang; Zhongpu Yin; Jianzhi Liu (BMC Biotechnology)
Abstract Background CUB domain-containing protein 1 (CDCP1), a type I transmembrane glycoprotein, is abundantly expressed in various cancers. However, its role and mechanism in nasopharyngeal carcinoma (NPC) remain ambiguous. Methods The UALCAN and GEPIA databases were analyzed to explore CDCP1 expression and survival prognosis in head and neck squamous cell carcinoma (HNSC) patients. Fifteen pairs of NPC tissues and adjacent normal tissues were collected for CDCP1 expression analysis. CCK-8 assays, flow cytometry, and transwell assays were performed on NPC cell lines (C666-1, 5–8 F, and HONE-1). The impact of GSK-3β inhibitor LiCl on C666-1 cells after CDCP1 knockdown was investigated. A C666-1 xenograft model was established for in vivo validation. Results CDCP1 was overexpressed in HNSC patients, and elevated CDCP1 correlated with poor survival. NPC tissues confirmed CDCP1 upregulation compared to normal tissues. CDCP1 knockdown in C666-1 and 5-8 F cells inhibited proliferation, migration, invasion, and promoted apoptosis, while LiCl partially reversed these effects. In vivo, CDCP1 silencing suppressed tumor growth, downregulated PCNA, Wnt3a, β-catenin, and p-GSK-3β, and upregulated cleaved caspase-3 and E-cadherin. CDCP1 overexpression in HONE-1 cells produced opposing effects. Conclusions In summary, CDCP1 promotes NPC progression via the Wnt/β-catenin pathway, suggesting its potential as a therapeutic target. Clinical trial number Not applicable.